Data Driven Decision Making For School Leadership: A Critical Analysis Of Supporting Systems - Sampson, Demetrios; Sergis, S. (2016)
Schools are complex adaptive systems comprising a vast range of interrelating agents including among others, the school principals, teachers, students, parents, and infrastructural assets. Therefore, school leaders are required to design the strategic plan of their schools by taking into account the full spectrum of the characteristics and behaviors of these agents and the complex manner in which they interrelate and affect the overall school performance. However, considering (a) the high complexity in collecting and processing the institution-wide data and towards generating feedback loops and (b) the wide range of the tasks that school leaders are expected to engage with, this data-driven decision-making process is challenging, and requires appropriate systems to support it. The contribution of this book chapter, therefore, is the critical analysis of 70 existing school leadership decision support systems (SL-DSS), in terms of their capacity to adequately support the full spectrum of school leadership tasks, as they are defined in this book chapter. This critical analysis aims to gather insights that could drive future implementations of SL-DSS toward providing more effective decision support affordances and tackling the identified shortcomings of existing systems.